The Influence of Digital Transformation, Market Orientation, and Strategic Differentiation on Marketing Performance (Survey on Cafes in Sukabumi City) - Serlina Aisyah; R. Deni Muhammad Danial; Dicky Jhoansyah (Al Qalam: Jurnal Ilmiah Keagamaan dan Kemasyarakatan, 2025)
Cafés are one of the rapidly growing culinary business sectors in Sukabumi City. Although many cafés emerge and initially go viral upon opening, a significant number experience a decline in performance afterward. This indicates issues in marketing performance, which may be influenced by several factors such as digital transformation, market orientation, and strategic differentiation. The purpose of this study is to examine the effect of digital transformation, market orientation, and strategic differentiation on the marketing performance of cafés in Sukabumi City. This research employs a quantitative method with a descriptive-associative approach. The population in this study consists of all café managers in Sukabumi City, with the sampling technique using purposive sampling involving 45 respondents. The results of the F-test (simultaneous) show that digital transformation, market orientation, and strategic differentiation simultaneously have a significant effect on marketing performance. The t-test (partial) results also indicate that digital transformation, market orientation, and strategic differentiation each have a significant effect on marketing performance.